The increasing trend in the consumption of ultra-processed food products is associated with a diet related to chronic diseases in Colombia-Evidence from national nutrition surveys 2005 and 2015. - Gustavo Cediel; Elisa María Cadena; Pamela Vallejo; Diego Gaitán; Fabio Da Silva Gomes (PLOS Global Public Health, 2024)
Introduction Ultra-processed food products (UPF) have been related to chronic diseases (CD). Public health politics has been establishing strategies to decrease the consumption of these products in the country. Objectives i) To assess the trend of the consumption of UPF between 2005 and 2015. (ii) its association with sociodemographic factors and the overall dietary content of nutrients related to CD in 2015. (iii) to estimate the Population Attributable Fraction of unhealthy nutrient intake in Colombia in 2015 due to ultra-processed food consumption. Methods We used data from the first (2005) and the last (2015) National Surveys of the Nutritional Status in Colombia. Food consumption was assessed using a 24-hour food recall. The NOVA classification classified the food items according to the extent and purpose of industrial processing. Results The consumption of processed and UPF increased in Colombia between 2005 and 2015. In 2015, no significant differences were found in the consumption of UPF between men and women but significant differences by age, wealth index, area of residence, and ethnicity (p<0.001). A significant positive association was found between the dietary share of UPF and the content of CD-related nutrients such as free sugars, total fats, saturated fats, trans-fats, and sodium. The prevalence of excessive intake of all CD-related nutrients (according to WHO recommendations) increased across quintiles of the dietary share of UPF. With the reduction of UPF consumption to the level seen among the 20% lowest consumers [1.0% (0-4.5%) of the total energy from UPF], the prevalence of excessive nutrient intake was almost three-fourths lower for trans fats; around one third lower for free sugar and saturated fats, 26% lower for sodium and 15% lower for total fat. Conclusions In Colombia, the increasing trend in the consumption of UPF is associated with increasing intake of CD-related nutrients. Thus, reducing the consumption of UPF is a potentially effective way to achieve the nutritional goals of the WHO for the prevention of CD.